Hepatoid carcinoma of the pancreas - Reis Soares, Mónica; Heitor, Suzana; Ribeiro, Adosinda; Esteves, Filomena; Morais, Luísa (Portuguese Journal Internal Medicine, 2012)
The authors describe a case of a 23-years-old male presenting weight loss, abdominal pain, fever and at a later stage, diarrhoea and vomiting. The patient was admitted to clarify the aetiology. On admission, a painful and distended abdomen with an epigastric mass and hepatomegaly were observed. The diagnosis was reached after several tests, including abdominal mass biopsy with a histological exam revealing a Hepatoid Carcinoma of the Pancreas. After a literature review we just find 8 cases described of this entity. We present the case and make a literature review about it.